Peran Mahasiswa MBKM Mengajar Mengaji untuk Membantu Siswa MI Darul Ulum Palangka Raya dalam Membaca Al-Qur’an dengan Baik - Ilham Panji Akbar; Istiyati Mahmudah; Siti Fatimah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
The purpose of MBKM student activities at MI Darul Ulum Palangka Raya is to help students learn to read the Qur'an. This study also involved teachers who teach Iqro and Al-Qur'an. This division is made to ensure that all activities are carried out correctly and instructions run smoothly until completion. The general and specific objectives of teaching the Quran are to build and develop individual Muslims who believe, fear Allah SWT, have noble character, and are useful for society. Students should be able to read the hijaiyah letters in order and correctly and memorize the sound of the reading. This is the ideal standard for the ability to read the Qur'an. Quran teaching activities take place for five days a week, starting after dawn, around 06.30-07.10 WIB. There are about 30 students taught by one teacher, MI Darul Ulum Palangka Raya teacher.